Indian economic crisis : a diagnostic study - Kurien, C. T. (London : Asia Publishing House, 1969)
This book is on Indian growth strategy bases on borrowed ideologies, borrowed theories and borrowing experiences.
Include index
oo 21/01/2019
Loans
Keywords: Economic policy; Economic history; India